Occupational Grade, Mental Distress, and the Use of Psychotherapy - Lauri Kokkinen; Kia Gluschkoff; Johanna Kausto; Sanna Selinheimo; Kaija Appelqvist-Schmidlechner; Päivikki Koponen; Ari Väänänen (SAGE Publishing, 2023)
Introduction: Previous studies have shown that manual workers use less psychotherapy than non-manual workers. However, little is known about the match between the use and the need of psychotherapy in different occupational grades. Our study investigates how the prevalence of mental distress corresponds to psychotherapy use rate in different occupational grades by gender. Methods: The data were collected from the Rise of Mental Vulnerability Study (use of psychotherapy) and the FinHealth 2017 Study (prevalence of mental distress). Adjusting for age, we calculated General Health Questionnaire (GHQ-12) caseness (a measure for mental distress), a 3-year psychotherapy use rate, and the ratio between GHQ caseness and the psychotherapy use rate in 3 occupational grades (upper non-manual employees, lower non-manual employees, and manual workers) for men and women separately. Results: In men, for 1 person having used psychotherapy there were 10 persons experiencing mental distress in upper non-manual workers, 14 in lower non-manual workers, and 31 in manual workers. In women, for 1 person having used psychotherapy, there were 6 persons experiencing mental distress in upper non-manual workers, 9 in lower non-manual workers, and 18 in manual workers. Conclusions: At the population level, manual employees use considerably less long-term psychotherapy than upper non-manual workers although their level of mental distress is high. This indicates a mismatch between symptoms and therapy, which was higher for men in all occupational grades.